2022
DOI: 10.4236/fns.2022.137049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cereal Malts Used as Improver on Physico-Chemical, Nutritional and Sensory Characteristics of Wheat and Millet Composites Breads

Abstract: The aim of this study was to optimize composite breads of wheat and whole millet flour by the use of natural improvers. Three types of local malted cereals were used as natural improvers. The millet flour was fermented with EPSs producing LAB strain prior to use. The technological characteristics of the composite flours were determined using an alveograph. The physicochemical and nutritional characteristics of the composite breads were determined using standard methods and their sensory profiles were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Pre‐processing techniques such as malting were applied on the inocula utilised in this study, apart from the wheat flour (W) which was used as it is. This process is a traditional technique that is well known to beneficially improve the composition of grains (Kewuyemi et al ., 2022; Tapsoba et al ., 2022; Vingrys et al ., 2022). The presence of hydrocarbons in SM, MM and MYM might be due to the auto‐oxidation of lipids in the grains, which may be caused by the activity of enzymes triggered during the malting process (Gasiński et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Pre‐processing techniques such as malting were applied on the inocula utilised in this study, apart from the wheat flour (W) which was used as it is. This process is a traditional technique that is well known to beneficially improve the composition of grains (Kewuyemi et al ., 2022; Tapsoba et al ., 2022; Vingrys et al ., 2022). The presence of hydrocarbons in SM, MM and MYM might be due to the auto‐oxidation of lipids in the grains, which may be caused by the activity of enzymes triggered during the malting process (Gasiński et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…These researchers found that in terms of the rheological properties of the dough, the use of malt flour as a source of enzymes gave better results than the commercially available enzyme. In addition to improving the rheological characteristics of the dough, the addition of malt had a positive effect on the fermentation properties of the dough, such as increasing the fermentation speed, the ability to retain gases, and a larger volume of the bread loaf [3,[27][28][29]. Malt also contributes to an increase in the content of reducing sugars, which may lead to a greater intensity of the Maillard reaction [25,30].…”
Section: Introductionmentioning
confidence: 99%